Inducing Development: Social Remittances and the Expansion of Oil Palm1. (March 2014) - Montefrio, Marvin Joseph F.; Ortiga, Yasmin Y.; Josol, Ma. Rose Cristy B.
This paper investigates the relationship between social remittances and land-use change in the context of South–South migration. Focusing on the cyclical movement of Filipino oil palm workers between the Philippine province of Palawan and the Malaysian State of Sabah, we show how migrants transmit social remittances, such as ideas of prosperity associated with oil palm development and knowledge of production practices and land impacts of oil palm plantations. These social remittances affect farmers' decisions to engage in oil palm development within the migrants' home province, possibly transforming subsistence agricultural systems into large-scale, monocrop plantations. We argue that such land development outcomes are an understudied aspect of how migration affects developing countries, especially in the context of South–South migration. Research findings also suggest how migrants' social remittances are transmitted, diffused, and utilized at broader social and political units, beyond return migrants' households and immediate communities in Palawan. Decision outcomes, however, are variable, with households and communities either engaging in or opposing oil palm development, depending on how social remittances are interpreted.